2013
DOI: 10.1007/s00431-013-2021-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of neurological manifestations in a boy with incontinentia pigmenti

Abstract: Incontinentia pigmenti (IP) is an X-linked dominant genodermatosis confined to females. It is usually lethal in males. However, the survival of some males has been reported in literature. We describe a long follow-up case of a 12-year-old male with IP and a normal karyotype but a genomic deletion of the NEMO gene in the Xq28 position in the form of somatic mosaicism. The patient showed severe ophthalmic abnormalities and neurological manifestations characterised by very mild cerebellar ataxia and a history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The patient showed severe ophthalmic abnormalities and neurological manifestations characterized by mild cerebellar ataxia and a history of epilepsy that was severe at the beginning with West syndrome, become moderate overtime and gradually resolved. Despite these neurological manifestations the longterm follow-up in this patient as reported by the authors, demonstrated good neurological and cognitive outcome [14]. It should be noted here that not all IP patients may have such an outcome.…”
Section: Discussionsupporting
confidence: 67%
“…The patient showed severe ophthalmic abnormalities and neurological manifestations characterized by mild cerebellar ataxia and a history of epilepsy that was severe at the beginning with West syndrome, become moderate overtime and gradually resolved. Despite these neurological manifestations the longterm follow-up in this patient as reported by the authors, demonstrated good neurological and cognitive outcome [14]. It should be noted here that not all IP patients may have such an outcome.…”
Section: Discussionsupporting
confidence: 67%
“…Somatic mosaicism refers to the occurrence of two genetically distinct populations of cells within an individual. On the other hand, hypomorphic or milder mutations in the IKBKG/NEMO gene, which result in the attenuation of NEMO function, can cause hypohidrotic ectodermal dysplasia with severe immunodeficiency (ectodermal dysplasia with immunodeficiency) . Large frame‐shift or deletion mutations that completely impair NEMO function lead to a lethal condition in male fetuses …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hypomorphic or milder mutations in the IKBKG/ NEMO gene, which result in the attenuation of NEMO function, can cause hypohidrotic ectodermal dysplasia with severe immunodeficiency (ectodermal dysplasia with immunodeficiency). 8 Large frame-shift or deletion mutations that completely impair NEMO function lead to a lethal condition in male fetuses. 9 A large deletion of exons 4-10 is found in approximately 80% of IP patients, whereas a small proportion of patients demonstrate mutations such as small nucleotide substitution, deletion and insertion.…”
Section: Discussionmentioning
confidence: 99%
“…De novo mutations, germline mosaicism and other complexities Although this concept of somatic mosaicism has been in the literature for many years [131][132][133][134][135], it is really only recently that more people are beginning to realize that it might be much more extensive in humans than previously thought [23,[136][137][138][139][140][141][142][143][144][145][146][147][148][149]. In fact, hardly anything is truly known regarding the extent of somatic mosaicism in humans and its effect on phenotype in even well studied diseases.…”
Section: "Those Who Have Given Any Attention To Congenital Mental Lesmentioning
confidence: 99%